(3OjhGf GdeJfHis - (3CMeO Hf GdMSjf Hf GdMSf Hf YHO GdUeO Hf GdLYaj Gdchaj GdeJfHj, CHh GdWjH, J (B354 (3g` s
(3ChdgG (B:s
(3PcQI GdOhdI Cf CHG GdWjH CMeO Hf GdMSjf GdeJfHi hdO HGdchaI ai cfOI s
(3BNQgG (B:s
(3bUjOI jgLQ ajgG GSMGb Hf cjZdZ bGdhG dfG eGJ GSMGb abdJ dge gPG GdOhGA GdPi jTai ef GdMeb s
(3GdfSNI HgG MhGTs
(3HgG SeGY Ydi CHj Gdjejf GdcfOis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B115 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B201s
(3JHUQGJ GdCUd (B:s
(3GdfSNI ebQhAI ef YGde eYQha (B: (3CHj SYO SYO Gddg Hf ZfGFe Hf Ydi Hf bGfJ GdbQi Gds
Keywords: (3GdCOHs